Development of Learning Media for Volleyball Subject Refereeing Subjects Based on Satellite E-Learning - Widianingsih, Onyas; Indrakasih, Indrakasih; Nugroho, Sinung; Sihombing, Hardodi (Budapest International Research and Critics University, 2021)
This research is a research on the development of learning media for the subject matter of the Volleyball subject matter based on e-learning satellite. This study discusses the role of learning media with technology. This study uses research from Borg and Gall through 10 stages including:(1) Preliminary Study, (2) Research planning, (3) Initial product development, (4) Initial (limited) field trials, (5) Revision of limited field test results, (6) wider field trials, (7) Revision of field test results, (8) Feasibility test, (9) Revision of feasibility test results, (10) Dissemination and socialization of final products. Results of this study: Small group test was carried out by testingdisplay of refereeing material Based on the value of the assessment questionnaire display of refereeing materialWith indicators of learning implementation assessment and material display, it is concluded that the questionnaire given to small groups has an effectiveness of implementing e-learning based refereeing learning by 55%. In other words, there is still much that needs to be improved so that the application used can have maximum effectiveness in the effectiveness of the assessment questionnaire pimplementationrefereeing learning based on e-learning It can be concluded that the questionnaire given to IT and Media experts has a display pimplementationrefereeing learning based on e-learning 56%.